Studi Pemberian Suplement MCT dengan Daya Terima dan Penambahan Berat Badan Anak Balita Penderita Diare di RSUP Dr. Kariadi Semarang - Novy Cahyani; Susi Tursilowati (JURNAL RISET GIZI, 2014)
Background: The occurrence of diarrhea is still high enough, every child which suffer from diarrhea 2-8 time a year with a mortality rate of 5 per 1000 under five years old children. MCT (Medium Chain Triglycerides) is the food given to patients Diarrhea. MCT can increase calories, digestion, absorption and dietary therapy with disease indications with the problem of poor digestion / malabsorption.Objective: To know the effect of adding MCT supplement and acceptance of the changes weight of children under five years old with diarrhea in RSUP. Kariadi of SemarangMethod: The study was a quasi experimental design with non-randomized control group pretest-posttest design. Its population was all patients with diarrhea in children aged 6-59 months who were treated in child Ward of RSUP Kariadi Semarang. Sample were collected using accidental method between October 2012 - January 2013. Seven children as samples with the treatment of supplements MCT addition and seven children as a comparison with placebo. Data was obtained through questionnaires and interviews covering the sample characteristics, energy intake,and the acceptance of pudding , MCT supplement intake, and weight. Analysis which used is the Independent T-test, Mann Whitney and Pearson and Spearman correlaton test.Results: There was no difference in the treatment group and the comparison group against acceptance of the pudding the value of p = 0.586 and it was also the weight change since the value of p = 0.427. There was the influence of the pudding in the treatment group received the weight change value of p = 0.029, in the comparison group received power there was no influence of the pudding to changes in the weight p = 0.105.Conclusion: There was no significant effect of acceptance of the pudding in the comparison group of changes in the weight but there was significant effect on the treatment of weight change